El uso de las TIC en la gestión de la información en la empresa M&V Ingenieros de la ciudad de Latacunga. - Quetamá García, Roberto Carlos. (2023)
The advance of ICT has given rise to the transformation in the way in which companies manage data and documents, in this way, the optimization of documentary processes, access and the care of their integrity is achieved, in this project we investigate the role of ICT (SGI) in the company M&V Ingenieros. As technology advances, the importance of including a platform that facilitates the efficient development of processes related to ensuring proper organizational functioning grows. The study was based on a quantitative methodology through the collection of numerical data, structuring surveys aimed at the entire population belonging to the aforementioned entity, the way in which control of the activities related to the life cycle is carried out was identified. of documents and workflows, that is, their execution is traditional, which is why the implementation of an Information Management System is important. The study determined the need to run software to facilitate organization, search and recovery. of data considerably reducing their times. The aim is to improve management through technological solutions to optimize the documentary processes in the company, the incorporation of the platform is crucial so that the entity can manage the information in an orderly manner and make decision making possible, generating a positive impact on productivity and the profitability of the organization. It is concluded that document management is not carried out in a systematic and integrated manner due to the lack of software that allows improving access and organization of information; the urgency of implementing a program that reduces time and errors is evident.